The Motives of Participation in Physical Activity at Al-Hussein City for Youth - Abedalbasit Abedalhafiz (My University, 2009)
The purpose of this study was to identify the most important motives of participation in physical activity among individuals who used to work out at Al-hussien city for youth, and the differences in motives according to gender, academic degree, social status, age, times of participation, and monthly income. A sample of (46) participants completed a 66-item questionnaire developed by the researcher to collect the data for this study. Findings indicated that the most important motives were as following: facilities availability motives (%78.77), other motives (%71.20), health and fitness motives (%71.15), mental motives (%65.54), athletic trends motives (%64.86), ethical traits motives (%63.62), psychological motives (%59.43), social motives (%41.79). Also, findings indicated no significant differences between motives according to academic degree, times of participation, and monthly income. In addition, results showed significant differences between male and female participants in social and trends motives, in favor of males. Moreover, there were significant differences between younger and older participants in social motives, in favor of older participants (above 50 years old).

هدفت هذه الدراسة إلى معرفة أهم دوافع ممارسة النشاط الرياضي عند مرتادي مدينة الحسين للشباب من جهة، واختلاف هذه الدوافع تبعا لمتغيرات: الجنس والمؤهل الاكاديمي والحالة الاجتماعية والعمر وعدد مرات ممارسة النشاط الرياضي ومستوى الدخل الشهري من جهة اخرى. استخدم الباحث استبانة مكونة من (66) فقرة، بلغت عينة الدراسة (46) فردا. وأشارت نتائج الدراسة الى ان دوافع ممارسة النشاط الرياضي لدى افراد عينة الدراسة حسب اهميتها جاءت على النحو التالي: الدوافع المتعلقة بالإمكانات المادية والتسهيلات (78,77%)، الدوافع الاخرى (71,20%)، دوافع اللياقة البدنية والصحية (71,15%)، الدوافع العقلية (65,54%)، دوافع الميول الرياضية (64,86%)، دوافع السمات اللاإرادية واللاأخلاقية (63,62 %)،الدوافع النفسية (59,43 %)، الدوافع الاجتماعية (41,79 %). كما أظهرت نتائج الدراسة عدم وجود فروق ذات دلالة إحصائية في دوافع ممارسة النشاط البدني لدى مرتادي مدينة الحسين للشباب تعزى لمتغيرات المؤهل الأكاديمي والحالة الاجتماعية وعدد مرات ممارسة النشاط الرياضي ومستوى الدخل الشهري. وأشارت نتائج الدراسة ايضا إلى وجود فروق ذات دلالة إحصائية تعزى لمتغيري الجنس في كل من محوري الدوافع الاجتماعية ودوافع الميول الرياضية لصالح الذكور والعمر في محور الدوافع الاجتماعية ولصالح الافراد الذين تزيد أعمارهم عن 50 عاما.
دوافع ممارسة النشاط الرياضي عند مرتادي مدينة الحسين للشباب